Corporate Social Responsibility And Firm Performance: An Empirical Analysis In Emerging Markets - Salsabila Andrina; Ranti Karlaili (BADAN PENERBIT STIEPARI PRESS, 2021)
This study conducts an empirical analysis to investigate the relationship between corporate social responsibility (CSR) practices and firm performance within emerging markets. Utilizing a comprehensive dataset from various industries and countries, we employ advanced econometric techniques to examine the impact of CSR activities on financial and non-financial performance metrics. Our findings suggest a positive correlation between CSR engagement and firm performance indicators, highlighting the potential benefits of CSR initiatives for companies operating in emerging markets. Specifically, we observe improvements in financial performance metrics such as profitability and market valuation, as well as enhanced non-financial outcomes including reputation and stakeholder satisfaction. These results underscore the importance of integrating CSR into corporate strategies as a means to achieve sustainable growth and competitive advantage in dynamic emerging market environments.